WHERE IS THE NICETY OF A SLOW RUSSIAN SPEECH? - Oleg A. Donskih (Высшее образование в России)
The paper shows the current decline in the quality of language skills, which is manifestedin the destruction of the linguistic code and the corres ponding depers onalization of communication. Historical experience shows that the national language enriches and develops under condition of a serious state attitude towards it.